LINGUISTIK MODERN (Model Pengkajian Kebudayaan) - Ali Badrudin (Adabiyyāt: Jurnal Bahasa dan Sastra, 2009)
Since the rise of the social science, in this case cultural studies, it has been difficult to determine the appropriate approach to analyze the social problems. The approach has close relation with the epistemology critic, which is unavoidable to the cultural studies, especially in the time where it handles the cultural variation facts. That the culture varies and that it gives the cultural studies a stimulus to adapt the modern linguistics are just a couple of facts. As a linguistics model, a cultural study has a powerful scientific base in the multi-variation of cultural data. The implication is so deep that it gives an orientation or a new perspective over a culture to be knowledgeable of human life. The use of modern linguistics approach (structural) in the cultural studies is related to Levi-Strauss ideas. He was the pioneer in the use of modern linguistics principles as models in order to know the cultural variations. The ambition of Levi-Strauss to build the cultural studies generates a scientific status for the study. It removes subjectivism, which ignores the essence of the meaning of culture. That ambition made structuralism a scientific study it is now although it is true that the modern linguistics creates the framework for the development of cultural studies. Yet, Structuralism has been criticized because it generates cultural studies to be mechanical.